A market‐financed and growth‐enhancing investment plan for the euro area. (17th June 2020) - Della Posta, Pompeo; Marelli, Enrico; Signorelli, Marcello
Abstract: In this paper, we analyze the problem of public debt‐to‐GDP stability in the Eurozone. We suggest that a feasible solution might be the realization of a market‐financed, growth‐enhancing investment program, which would be particularly welcome because of the positive short‐ and long‐term repercussions it would have on GDP growth and the stabilizing effects on interest rates. Some simulations allow us to quantify these effects. The consequences of the COVID‐19 pandemic further reinforce our policy implications in terms of public debt sustainability.